PENDAMPINGAN PENGELOLAAN KEUANGAN DAN PENYUSUNAN LAPORAN KEUANGAN SEKOLAH BAGI PEMILIK SEKOLAH DAN PENGELOLA KEUANGAN SEKOLAH DI WILAYAH BOGOR - Etty Murwaningsari; Sofie Sofie; Sistya Rachmawati; Fatik Rahayu (Universitas Trisakti, 2021)
Abstract:This community service activity aims to help school owners and managements to get competences in preparing Financial Statement regarding to Accounting Standards for Non Profit Entity (PSAK 45/ISAK 35). The subject discussed in this community service activity are: 1. Basic knowledge of Financial Statement for Non Profit Entity, 2. The Accounting Cycle Concept that consist of journalization, posting to general legder, preparing trial balance, adjusting entries concept, and adjusted trial balance. 3. Basic concept of preparing Financial Statements including activity statement, statement of financial position, and cash flow statement. 4. Practise for identifying transaction, preparing cash journal, posting to general ledger, and preparing trial balance. 5. This community service activity is a suistanable training program, with objective to give the participants competences in preparing Financial Statements of their school at the end of the program. Methods used in this community service activity are counseling, training, and mentoring presented by community service activity team. Discussion sessions with participants guided by the mentor and held in Zoom Meeting. Questionnaire in Google Form platform is used to gather feedback from participants. The evaluation results for this community service activity, both during the session and through questionnaire, shows that participants are satisfied with the program and the purpose of this community service activity is achieved where participants got the benefits in knowledge, understanding, and skills related to Financial Management and Financial Statements in school. Also, participants are able to apply transaction identification, journalized, prepared general ledger and trial balance.